2009
DOI: 10.1002/ijc.24262
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pentose phosphate pathway during cell cycle progression in human colon adenocarcinoma cell line HT29

Abstract: Cell cycle regulation is dependent on multiple cellular and molecular events. Cell proliferation requires metabolic sources for the duplication of DNA and cell size. However, nucleotide reservoirs are not sufficient to support cell duplication and, therefore, biosynthetic pathways should be upregulated during cell cycle. Here, we reveal that glucose-6-phosphate dehydrogenase (G6PDH) and transketolase (TKT), the 2 key enzymes of oxidative and nonoxidative branches of the pentose phosphate pathway (PPP), respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 48 publications
2
80
0
1
Order By: Relevance
“…92 Some studies have reported that the non-oxidative arm of PPP is the principal pathway for R5P synthesis in tumor cells 25,62,92. after finding a significant overexpression of the transketolase-like 1 (TKTL1) enzyme in progressing tumors. 96 However, other reports have indicated that both G6PDH and TKTL1 are overexpressed during the cell cycle progression of a human colon cancer cell line 97 and in (pre)neoplastic lesions in rat liver. 98 It is likely that cancer cells acquire diverse energy supplies that are differentially regulated during the development of the disease.…”
Section: Tumor Cells Synthesize Fatty Acids and Nucleotides At High Rmentioning
confidence: 98%
“…92 Some studies have reported that the non-oxidative arm of PPP is the principal pathway for R5P synthesis in tumor cells 25,62,92. after finding a significant overexpression of the transketolase-like 1 (TKTL1) enzyme in progressing tumors. 96 However, other reports have indicated that both G6PDH and TKTL1 are overexpressed during the cell cycle progression of a human colon cancer cell line 97 and in (pre)neoplastic lesions in rat liver. 98 It is likely that cancer cells acquire diverse energy supplies that are differentially regulated during the development of the disease.…”
Section: Tumor Cells Synthesize Fatty Acids and Nucleotides At High Rmentioning
confidence: 98%
“…In agreement with the present study, Frederiks et al (2007) reported a massive ultrastructural localization of G-6-PD in the cytoplasm of colon carcinoma cells, whereas human colon cancer cells contained five times higher G-6-PD activity than hepatoma cells. Vizán et al (2009) found that G-6-PD, the key enzyme of the oxidative branch of the pentose phosphate pathway (which is necessary for nucleotide synthesis), is enhanced during cell cycle progression of the human colon cancer cell line. This enhanced enzyme activity coincides with an increased ratio of the pentose monophosphate to the hexose monophosphate pool during late G1 and S phases of cell cycle, suggesting a potential role for pentose phosphates in proliferation signalling.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigations have dealt with pyruvate kinase (PK) activity among different grades of malignancy in colorectal cancer (Shin et al 2009). Glucose-6-phosphate dehydrogenase (G-6-PD) has also been reported in a human adenocarcinoma cancer cell line (Vizán et al 2009). …”
mentioning
confidence: 99%
“…This observation reflects the well-known fact that immunoblotting techniques are more sensitive detection methods than mass spectrometry, particularly for low abundance proteins. G6PD is the key regulatory enzyme in PPP and necessary for the synthesis of nucleotides and nucleic acids (39)(40)(41). Recent studies have demonstrated that G6PD activity is suppressed in cells containing wild-type p53 through a direct inhibition; whereas, it is not subjected to such negative regulation in cells containing mutant p53 (42).…”
Section: Discussionmentioning
confidence: 99%